Narrating Climate Change: Conventionalized Narratives in Concordance and Conflict - Andersson, Daniel; Cocq, Coppélie (Narrative Works)

(untitled) (The University of New Brunswick, 2016)
In this article, we take a narrative approach to Swedish media texts regarding farming, forestry, and Sami livelihoods. The main purpose is to illuminate how a master narrative on climate change is shaped, activated, and put into practice in different ways in different settings and contexts. The study discusses the complex interplay between different levels of narratives and the narrative dynamics that influence and shape collective representations of climate change. We discern a narrative level that does not explicitly challenge the master narrative, but operationalizes it in close relation to cultural contexts and specific goals, resulting in what we call conventionalized narratives.